HIIT Training Mentoring to Improve Speed and Agility for MMA Athletes at Camp Monster Karo - Julius Boy Nesra Basgimata Barus; Janwar Frihasan Sinuraya; Agavetra Tarigan; Egin Ginting (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Speed and agility are vital physical fitness components for Mixed Martial Arts (MMA) athletes; however, unstructured training programs remain a common challenge in many MMA communities, including Camp Monster Karo, Karo Regency, North Sumatra. This community service activity aimed to provide High-Intensity Interval Training (HIIT) coaching to improve the speed and agility of MMA athletes while strengthening the coach's competence in designing science-based training programs. The activity was conducted over eight weeks using a Community Development approach integrated with Participatory Action Research (PAR), involving 12 active athletes and 1 coach. The HIIT program was implemented for six weeks (18 sessions) incorporating sprint drills, agility drills, and sport-specific drills at 85–95% HRmax intensity. Evaluation was conducted using the 30-meter sprint test and the Illinois Agility Test. Results showed an average improvement in speed of 6.05% (t = 4.827, p = 0.000) and agility of 8.48% (t = 6.214, p = 0.000). The coach's understanding of HIIT principles increased by 143%. The program proved effective in improving athletes' physical performance and produced a paradigm shift in training culture toward a sustainable, evidence-based approach.